Značilnosti igranja športnih stav pri študentih ekonomskih smeri - Kovač, Janez (Šport (Ljubljana), 2018)
The article is discussing purchasing habits on sports betting among Economics students. The purpose of the research was determining how many students already participated in betting and how many of them are betting regularly. We were interested in frequency of betting, where students learned about betting, motives behind betting, amount used, style of betting, place of betting and betting provider. Data was acquired among students of Faculty of Economics Ljubljana, Faculty of Economics and business Maribor, Faculty of Organizational Sciences Kranj and Faculty of Management Koper between 08.04.2017 and 04.05.2017. 216 answers were acquired via anonymous web questionnaire. Research has shown that majority of students already has some betting experiences. Most of them only bets few times a year and their source were friends. Most common motive for betting is profit. More than 50% of all participants bets no more than 10 EUR in most common betting place gas stations. Gender analysis showed that man bet more often, even more so when they are single or living in non-marital partnerships. Research also concluded that betting frequency decreases with higher number of family members. Furthermore, betting was most present with students living in dormitories. We were unable to prove any statistical differences in connection with monthly income, type of faculty, degree of study or type of study.
Keywords: igre na srečo; motivi za igranje; nakupne navade; slog igranja; športne stave; študenti